Experimental and Numerical Analyses of Buried HDPE Pipe with Using EPS Geofoam - Akyelken, Furkan A.; Kilic, Havvanur (KOREAN SOCIETY OF CIVIL ENGINEERS-KSCE, 2022)
High density polyethylene (HDPE) pipes are generally not used in applications that will be exposed to high filling stresses. For this reason, there are not enough experimental and numerical analysis studies in the literature on the reduction of stresses on HDPE pipes with soft zone application. In this study, it was aimed to evaluate the performance of imperfect trench installations containing soft material zone for buried HDPE pipe by numerical analysis. Laboratory-scale experiments and numerical analyses were conducted to study the performance of the HDPE pipe with soft zone application. A surcharge load was applied to the backfill, and earth pressure and soil settlements around the HDPE pipe and pipe deflections were measured for two soft zone geometries. After validation of the test results by a numerical method, parametric studies were performed to investigate the change of EPS Geofoam material and backfill soil type. According to the results, it was seen that the horizontal and vertical stresses acting on the pipe decreased by 65%-70% in accordance with the experimental measurements. It has been determined that the deformations of pipes under 10m filling load do not exceed 1%. Experimental and numerical results show that by applying a soft zone around the HDPE pipe, the stresses acting on the side wall of the pipe are significantly reduced, and the behavior of the pipe is not affected much by the infill soil type.
Keywords: EPS Geofoam; Buried pipe; Numerical analysis; Imperfect trench method; HDPE; Arching factor; IMPERFECT TRENCH INSTALLATIONS; EXPANDED POLYSTYRENE; Engineering